Effects of Lipopolysaccharide-Binding Protein (LBP) Single Nucleotide Polymorphism (SNP) in Infections, Inflammatory Diseases, Metabolic Disorders and Cancers - Meng, Leilei; Song, Zichen; Liu, Anding; Dahmen, Uta; Yang, Xiao; Fang, Haoshu (Frontiers in Immunology, 2021)
Inflammation, which is induced by the immune response, is recognized as the driving factor in many diseases, including infections and inflammatory diseases, metabolic disorders and cancers. Genetic variations in pivotal genes associated with the immune response, particularly single nucleotide polymorphisms (SNPs), may account for predisposition and clinical outcome of diseases. Lipopolysaccharide (LPS)-binding protein (LBP) functions as an enhancer of the host response to LPS, the main component of the outer membrane of gram-native bacteria. Given the crucial role of LBP in inflammation, we will review the impact of SNPs in the LBP gene on infections and inflammatory diseases, metabolic disorders and cancers.